Evaluating Synergies and Trade-Offs among Sustainable Development Goals (SDGs): Explorative Analyses of Development Paths in South Asia and Sub-Saharan Africa - Brijesh Mainali; Jyrki Luukkanen; Semida Silveira; Jari Kaivo-oja (MDPI, 2022)
Understanding the linkages between multiple targets of Sustainable Development Goals (SDGs) may help to integrate different sectoral programmes and develop coherent cross-sectoral policy to explore synergies. Synergy is interaction among two or more actions, which will lead to an impact greater or less than the sum of individual effects. Therefore, synergy can be positive or negative (trade-off). This paper aims at developing an analytical framework to evaluate sectoral linkages and examine potential synergies and trade-offs among various SDGs’ goals and targets. Synergies and trade-offs related to energy access (SDG7), clean water and sanitation access (SDG6), food security and sustainable agriculture (SDG2) and poverty alleviation (SDG1) have been evaluated from the perspective of developing countries using examples from South Asia (Bangladesh, Nepal, and Sri Lanka) and Sub-Saharan Africa (Ghana, Ethiopia and Rwanda), and historical data for the period between 1990 and 2012. The analytical framework includes both qualitative and quantitative methods. Network analysis technique has been used for exploring the conceptual linkage among different indicators, and capturing the targets associated with SDGs. Advanced Sustainability Analysis (ASA) developed under the European framework programme has been used for quantifying the synergies and trade-offs among sustainability indicators. The analysis showed strong synergy among various SDG targets. Interestingly, the potential synergy differs from country to country and over time. Ghana and Sri Lanka had relatively higher potential synergy, whereas Rwanda and Nepal had relatively lower potential synergy among the various targets. Higher synergy values were evidenced in those cases where the policy have recognized and emphasized on linkages among cross-sectoral targets.